calculus infography
Avatar
CalculusPop
CalculusPop
Hey, let's solve some calculus with CalculusPop
 
Differentiation

To differentiate a product of two functions, we can use the product rule.

The product rule states that if we have two functions, f(x) and g(x), the derivative of their product is given by:

\frac{d}{dx}(f(x) \cdot g(x)) = f'(x) \cdot g(x) + f(x) \cdot g'(x)

Where:

- f(x) is the first function
- g(x) is the second function
- f'(x) is the derivative of the first function
- g'(x) is the derivative of the second function

To differentiate a product of two functions:

1. Identify the first function f(x) and the second function g(x).
2. Calculate the derivative of f(x) and g(x) separately.
3. Apply the product rule formula: \frac{d}{dx}(f(x) \cdot g(x)) = f'(x) \cdot g(x) + f(x) \cdot g'(x).
4. Simplify the expression if necessary.

Question 1

Find the derivative of y = x^2 \cdot e^x.

Solution:

Given y = x^2 \cdot e^x, we need to find \frac{dy}{dx}.

Using the product rule of differentiation, we have:

\frac{dy}{dx} = 2x \cdot e^x + x^2 \cdot e^x

\frac{dy}{dx} = x(2 + x) \cdot e^x

Therefore, \frac{dy}{dx} = x(2 + x) \cdot e^x.

Question 2

Differentiate f(x) = \sin(x) \cdot \cos(x).

Solution:

Given f(x) = \sin(x) \cdot \cos(x), we need to find f'(x).

Applying the product rule, we have:

f'(x) = \cos(x) \cdot \cos(x) + \sin(x) \cdot (-\sin(x))
f'(x) = \cos^2(x) - \sin^2(x)
f'(x) = \cos(2x)

Therefore, f'(x) = \cos(2x).

Question 3

Differentiate the function f(x) = x^2 \cdot \sin(x) with respect to x.

Solution:

To differentiate a product of two functions, we use the product rule:

Let u(x) = x^2 and v(x) = \sin(x).

Then, the product rule states that \frac{d}{dx}(u(x)v(x)) = u'v + uv'.

Now, differentiate u(x) = x^2 with respect to x:

u'(x) = 2x.

Differentiate v(x) = \sin(x) with respect to x:

v'(x) = \cos(x).

Applying the product rule, we have:

\frac{d}{dx}(x^2 \cdot \sin(x)) = 2x \cdot \sin(x) + x^2 \cdot \cos(x).

Therefore, the derivative of f(x) = x^2 \cdot \sin(x) with respect to

x is 2x \cdot \sin(x) + x^2 \cdot \cos(x).

Question 4

Find the derivative of y = e^x \cdot \cos(x) with respect to x.

Solution:

To differentiate the product of two functions, we apply the product rule.

Let u(x) = e^x and v(x) = \cos(x).

Then, the product rule states that \frac{d}{dx}(u(x)v(x)) = u'v + uv'.

Differentiate u(x) = e^x with respect to x:

u'(x) = e^x.

Differentiate v(x) = \cos(x) with respect to x:

v'(x) = -\sin(x).

Applying the product rule, we get:

\frac{d}{dx}(e^x \cdot \cos(x)) = e^x \cdot (-\sin(x)) + e^x \cdot \cos(x).

Therefore, the derivative of y = e^x \cdot \cos(x) with respect to x is e^x (\cos(x) - \sin(x)).

Question 5

Determine the derivative of y = x \cdot e^{2x} with respect to x.

Solution:

To differentiate the product of two functions, we apply the product rule.

Let u(x) = x and v(x) = e^{2x}.

Then, the product rule states that \frac{d}{dx}(u(x)v(x)) = u'v + uv'.

Differentiate u(x) = x with respect to x:

u'(x) = 1.

Differentiate v(x) = e^{2x} with respect to x:

v'(x) = 2e^{2x}.

Applying the product rule, we have:

\frac{d}{dx}(x \cdot e^{2x}) = 1 \cdot e^{2x} + x \cdot 2e^{2x}.

Therefore, the derivative of y = x \cdot e^{2x} with respect to x is

e^{2x} + 2xe^{2x}.

Question 6

Find the derivative of f(x) = \ln(x) \cdot x^3 with respect to x.

Solution:

To differentiate the product of two functions, we apply the product rule.

Let u(x) = \ln(x) and v(x) = x^3.

Then, the product rule states that \frac{d}{dx}(u(x)v(x)) = u'v + uv'.

Differentiate u(x) = \ln(x) with respect to x:

u'(x) = \frac{1}{x}.

Differentiate v(x) = x^3 with respect to x:

v'(x) = 3x^2.

Applying the product rule, we get:

\frac{d}{dx}(\ln(x) \cdot x^3) = \frac{1}{x} \cdot x^3 + \ln(x) \cdot 3x^2.

Simplify to find the derivative:

\frac{d}{dx}(\ln(x) \cdot x^3) = x^2 + 3x^2 \ln(x).

Thus, the derivative of f(x) = \ln(x) \cdot x^3 with respect to x is

x^2 + 3x^2 \ln(x).

Question 7:

Differentiate the function y = \sqrt{x} \cdot e^x with respect to x.

Solution:

To differentiate the product of two functions, we apply the product rule.

Let u(x) = \sqrt{x} and v(x) = e^x.

Then, the product rule states that \frac{d}{dx}(u(x)v(x)) = u'v + uv'.

Differentiate u(x) = \sqrt{x} with respect to x:

u'(x) = \frac{1}{2\sqrt{x}}.

Differentiate v(x) = e^x with respect to x:

v'(x) = e^x.

Applying the product rule, we have:

\frac{d}{dx}(\sqrt{x} \cdot e^x) = \frac{1}{2\sqrt{x}} \cdot e^x + \sqrt{x} \cdot e^x.

Simplify to find the derivative:

\frac{d}{dx}(\sqrt{x} \cdot e^x) = \frac{e^x}{2\sqrt{x}} + \sqrt{x} \cdot e^x.

Therefore, the derivative of y = \sqrt{x} \cdot e^x with respect to x is

\frac{e^x}{2\sqrt{x}} + \sqrt{x} \cdot e^x.

Questions

1. \frac{d}{dx}(f(x)g(x))

2. \frac{d}{dx}(3x^2 \cdot \sin(x))

3. \frac{d}{dx}(e^x \cdot \cos(x))

4. \frac{d}{dx}(2x \cdot \ln(x))

5. \frac{d}{dx}(x^3 \cdot e^{2x})

6. \frac{d}{dx}(4x \cdot \tan(x))

7. \frac{d}{dx}(6x^2 \cdot \sqrt{x})

8. \frac{d}{dx}(\ln(x) \cdot e^x)

9. \frac{d}{dx}(2x^3 \cdot \sin(2x))

10. \frac{d}{dx}(x \cdot \cos(x))

11. \frac{d}{dx}(4x^2 \cdot e^x)

12. \frac{d}{dx}(e^{3x} \cdot \tan(x))

13. \frac{d}{dx}(5x \cdot \ln(2x))

14. \frac{d}{dx}(x^4 \cdot \cosh(x))

15. \frac{d}{dx}(e^{-x} \cdot \sin(x))

Answer:

1. g(x)+f(x)g'(x)

2. 6x\sin(x)+3x^2\cos(x)

3. e^x\cos(x)-e^x\sin(x)

4. 2\ln(x)+2

5. 3x^2e^{2x}+2x^3e^{2x}

6. 4\tan(x)+4x\sec^2(x)

7. 12x\sqrt{x}+3x^2\sqrt{x}

8. \frac{1}{x}e^x+\ln(x)e^x

9. 6x^2\sin(2x)+4x^3\cos(2x)

10. \cos(x)-x\sin(x)

11. 4x^2e^x+8xe^x

12. 3e^{3x}\tan(x)+e^{3x}\sec^2(x)

13. 5\ln(2x)+5 [\frac{1}{x}]

14. 4x^3\cosh(x)+x^4\sinh(x)

15. -e^{-x}\sin(x)-e^{-x}\cos(x)

Previous Lesson
Next Lesson

Classroom: Differentiation of a Product

\frac{d}{dx}(f(x) \cdot g(x)) = f'(x) \cdot g(x) + f(x) \cdot g'(x)

Calculus Archives

Useful Calculus links

Differentiate 4 sin(x)With Steps
To differentiate the function 4 sin(x) with respect to x, we apply the rules of differentiation. The...
Differentiation Solver AI
CalculusPop differential calculus AI solver that can handle a variety of differentiation problems. It...
Differentiate 3In5x With Steps
To differentiate the expression 3ln5x with respect to x, we will use the chain rule of differentiation....
Differentiate -1/√x With Steps
The differentiation of the function -1/√x involves using the power rule for differentiation. By rewriting...
Differentiate - x^(1/2)
To differentiate - x^{1/2} with respect to x, we can use the power rule of differentiation. This rule...
Ads Blocker Image Powered by Code Help Pro

Ads Blocker Detected!!!

We have detected that you are using extensions to block ads. Please support us by disabling these ads blocker.

Powered By
Best Wordpress Adblock Detecting Plugin | CHP Adblock